2017
DOI: 10.5301/jva.5000710
|View full text |Cite
|
Sign up to set email alerts
|

Advanced age is not a barrier to creating a functional arteriovenous fistula: a retrospective study

Abstract: We found no difference in AVF maturation, primary patency, complications, or interventions in those over the age of 75 compared to younger counterparts. While secondary and functional patency rates were significantly lower in those aged >75 years, the magnitude of difference is likely not clinically relevant. Therefore, we recommend that advanced age alone should not preclude patients from AVF creation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Although age has been reported as an independent risk factor for AVF failure, 21 several studies have failed to confirm a negative correlation between age and AVF outcome. [22][23][24] In our study, age had no effect over any measured outcome, including primary patency (odds ratio [OR], 1.03; 95% CI, 0.97-1.09; P = 0.4), secondary patency (OR, 1.05; 95% CI, 0.98-1.12; P = 0.1), functional patency (OR, 0.97; 95% CI, 0.91-1.02; P = 0.3), vein diameter (β = −0.002; 95% CI, −0.09 to 0.08; P = 0.9; R 2 = 0.0001), or volume flow rate (β = −6.5; 95% CI, −21.5 to 8.37; P = 0.4; R 2 = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…Although age has been reported as an independent risk factor for AVF failure, 21 several studies have failed to confirm a negative correlation between age and AVF outcome. [22][23][24] In our study, age had no effect over any measured outcome, including primary patency (odds ratio [OR], 1.03; 95% CI, 0.97-1.09; P = 0.4), secondary patency (OR, 1.05; 95% CI, 0.98-1.12; P = 0.1), functional patency (OR, 0.97; 95% CI, 0.91-1.02; P = 0.3), vein diameter (β = −0.002; 95% CI, −0.09 to 0.08; P = 0.9; R 2 = 0.0001), or volume flow rate (β = −6.5; 95% CI, −21.5 to 8.37; P = 0.4; R 2 = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…However, when primary failure is accounted for, patency rates dropped to 71% at 1 year and 64% at 2 years. A recent Canadian study also found that fistulas created in patients older than 75 have significantly reduced secondary patency . The results of the recently published FAVORED trial, in which 47% of newly created fistulas failed within the first year, highlight the significant impact of primary/early failure on fistula longevity …”
Section: Vascular Access Should Be Reliable and Durablementioning
confidence: 97%
“…At least 12.6% of angioplasties performed in the United States between 2001 and 2015 were done to promote maturation in fistulas with primary failure . A 2017 single‐center study showed that 49% of fistulas require intervention to maintain patency in the first year after creation, and 78% require intervention in the first 3 years …”
Section: Vascular Access Should Be Reliable and Durablementioning
confidence: 99%
“…In contrast, a multicenter prospective study on 395 patients undergoing HD demonstrated that an age of ≥ 65 years was not associated with the primary functional loss of AVF patency [hazard ratio (HR) 1.49, 95% CI 0.96-2.31] [18]. Further, a recent retrospective study on 525 patients who underwent AVF constructions and who were stratified by age (< 65, 65-75, and > 75 years) revealed that no significant differences in the incidence of primary VAF or primary patency after 1-3 years [19]. These findings suggested that VAF occurs frequently in elderly patients because the blood flow of AVF in the elderly was lower than that in non-elderly patients possibly due to atherosclerosis with aging [14,15,20].…”
Section: Agementioning
confidence: 99%